2017
DOI: 10.1080/00423114.2017.1318212
|View full text |Cite
|
Sign up to set email alerts
|

Wheel slip control with torque blending using linear and nonlinear model predictive control

Abstract: Modern Hybrid Electric Vehicles employ electric braking to recuperate energy during deceleration. However, currently Anti-lock Braking System (ABS) functionality is delivered solely by friction brakes. Hence regenerative braking is typically deactivated at a low deceleration threshold in case high slip develops at the wheels and ABS activation is required. If blending of friction and electric braking can be achieved during ABS events, there would be no need to impose conservative thresholds for deactivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…The same authors state that "the simulation and test results demonstrated that the l1-optimal hybrid controller used in this problem can lead to about 20% reduction in peak slip amplitudes and corresponding spin duration when compared to best case linear MPC counterparts." Similarly, [17] shows the superiority of NMPC over linear MPC in terms of slip control performance. The necessity of "objective benchmarking technologies" in the field of ABS / TC was pointed out in the survey study in [19].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The same authors state that "the simulation and test results demonstrated that the l1-optimal hybrid controller used in this problem can lead to about 20% reduction in peak slip amplitudes and corresponding spin duration when compared to best case linear MPC counterparts." Similarly, [17] shows the superiority of NMPC over linear MPC in terms of slip control performance. The necessity of "objective benchmarking technologies" in the field of ABS / TC was pointed out in the survey study in [19].…”
Section: Introductionmentioning
confidence: 90%
“…In this study a multi-parametric quadratic programming (mp-QP) formulation is adopted, as suggested in [21] and implemented in [24]. The mp-NLP in (13) and (14) is linearized around a predefined point ( 0 , ,0 ) by means of Taylor series expansion, such that the cost function is approximated with a quadratic function (15)- (16) and the constraints assume a linear formulation (17):…”
Section: B Off-line Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…torque blending, and compares the NMPC simulation results with those from a linear MPC. In addition to the better performance of the nonlinear solution, [23] reports that the computational time for the NMPC is of 3-4 ms on a desktop personal computer, whereas the linear MPC requires ~1 ms. In [24] an implicit NMPC slip control strategy is assessed in simulation, and implemented on a quad-core 2.8 GHz dSPACE unit yielding a computational time of 4-5 ms. [25] shows that the implementation time step is more influential than the selected control technology (NMPC or PID) on the performance of a traction controller for an electric vehicle with in-wheel motors.…”
mentioning
confidence: 99%
“…Hence, it is desirable to have a controller capable of a rather smooth wheel slip control action, without the typical chattering issues of sliding mode controllers.  Because of its explicit nature, the specific ABS eNMPC of this study requires only a fraction of the computing time (i.e., < 0.1 ms on a 900 MHz dSPACE automotive platform) of the implicit solutions in [23,24], and therefore can run at much smaller time steps than an equivalent implicit NMPC.  In eNMPC the explicit solution is known in advance, which allows carrying out a systematic a-priori analysis of the control system performance, with benefits in terms of functional safety of the automotive system, with respect to implicit NMPC.…”
mentioning
confidence: 99%